Multi‐attribute analysis of investments risk alternatives in construction - Shevchenko, Galina; Ustinovichius, Leonas; Andruškevičius, Algirdas (Technological and Economic Development of Economy, 2008)
In project development it is hardly possible to get exhaustive and accurate information. As a result, the situations occur, the consequences of which can be very damaging to the project. Inaccurate evaluation of the strategy related to capital investment and project implementation is one of the reasons why such estimates are not required in practice. Instead, a classification approaches may be used for this purpose. The decision‐making process, based on the established risk assessment principles expressed in linguistic terms, requires qualitative judgement and experiential knowledge of the construction experts. Presented structured and realistic methods deals systematically with different risk management situations and assist the investors in reaching the correct risk assessment of possible alternatives will be of great value. This paper presents a methods of multiattribute comparativite analysis (CLARA and SAW methods) of variants of investment classified risks in construction. A practical case to illustrate how the methods works is presented.Statybos alternatyvų investicinės rizikos daugiatikslė analizė taikant SAW ir CLARA metodusSantrauka. Šiame straipsnyje nagrinėjamos daugiatikslės analizės metodų taikymo galimybės. Svarbus investicijų efektyvumo garantas yra nuodugni investicinių projektų analizė ir vertinimas. Tai leidžia pagal tam tikrus kriterijus nustatyti investavimo variantų efektyvumą. Vertinimo kriterijai turi būti grindžiami tiek investicinį projektą įgyvendinančio subjekto, tiek investuotojo interesais. Analizuojant investicinius procesus yra susiduriama su įvairaus pobūdžio informacija – kokybinė ir kiekybinę. Šiame straipsnyje yra siūlomi du metodai, analizuojantys (įvertinantys) investicinę riziką – SAW ir CLARA metodai. Pateikti metodų pritaikymo rezultatai.Reikšminiai žodžiai: ekspertinės sistemos, sprendimų priėmimas, verbalinės analizės metodai,CLARA, SAW.First published online: 21 Oct 2010